2022
DOI: 10.3389/fendo.2022.857947
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Hypercortisolism and Glucose-Metabolism Disturbances in Patients with Mild Autonomous Cortisol Secretion: Findings From a Single Center in China

Abstract: Background and objectiveMild autonomous cortisol secretion (MACS) presents with a marked female preponderance, but whether the sex difference in its distribution has any relevance to the presentation and outcome of the disease is unknown. The aim of this study was therefore to compare biochemical indices of hypercortisolism and impaired glucose metabolism between male and female patients with MACS.MethodWe enrolled a total of 98 patients with autonomous/possible autonomous cortisol secretion in our study, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This finding is in line with the results of a recent cross-sectional large multicenter study including 4374 patients with AI, which showed a significant increase of all-cause mortality and major adverse cardiovascular event (MACE) in female patients younger than 65 years with autonomous cortisol secretion ( 9 ). Moreover, a monocentric study including 98 patients with MACS reported only in premenopausal women a direct correlation between autonomous cortisol secretion levels and levels of fasting C-peptide or fasting C-peptide-to-glucose ratio, which are considered indexes of insulin resistance ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the results of a recent cross-sectional large multicenter study including 4374 patients with AI, which showed a significant increase of all-cause mortality and major adverse cardiovascular event (MACE) in female patients younger than 65 years with autonomous cortisol secretion ( 9 ). Moreover, a monocentric study including 98 patients with MACS reported only in premenopausal women a direct correlation between autonomous cortisol secretion levels and levels of fasting C-peptide or fasting C-peptide-to-glucose ratio, which are considered indexes of insulin resistance ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…One is highlighted by the existence of individuals showing null effects of AGI on reducing their glucose excursions. Causes of elevated glucose levels include stress hormones associated with not only insulindependent endocrine systems but also the central nervous system, such as cortisol (Ortiz et al, 2019;Bentele et al, 2021;Ouyang et al, 2022). Further studies are needed to explore the mechanism by which glycemic dysregulation occurs in such individuals.…”
Section: Discussionmentioning
confidence: 99%